2015
DOI: 10.1016/j.jth.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

An intervention encouraging planned self-regulation and goal setting in drivers across the lifespan: Testing an extended theory of planned behaviour

Abstract: Previous work has demonstrated that planning behaviours may be more adaptive than avoidance strategies in driving self-regulation, but ways of encouraging planning have not been investigated. The efficacy of an extended Theory of Planned Behaviour (TPB) plus implementation intention based intervention to promote planning self-regulation in drivers across the lifespan was tested. An age stratified group of participants (N=81, aged 18 to 83 years) was randomly assigned to an experimental or control condition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…Another possible reason for our success was the use of extended TPB. Previous studies mentioned the effectiveness of educational interventions by extended TPB [55,56]. Results of our study indicated that attitude scores significantly increased in the experimental group after the intervention compared to the control group.…”
Section: Discussionsupporting
confidence: 46%
“…Another possible reason for our success was the use of extended TPB. Previous studies mentioned the effectiveness of educational interventions by extended TPB [55,56]. Results of our study indicated that attitude scores significantly increased in the experimental group after the intervention compared to the control group.…”
Section: Discussionsupporting
confidence: 46%
“…Perceived behavioral control, similar to self-efficacy, reflects an individual's strong control belief in conquering difficulties and in performing a certain action, whereas intention is the direct factor influencing environmental behaviors [22,23]. A motive is always accompanied by a goal, so intention alone cannot fully reflect the motivation direction without the introduction of the goal [24,25]. As for the motivation persistence, the existence of habits for routine behavior has considerable effects on travel mode choice.…”
Section: Travel Mode Choice and Multiple Motivationsmentioning
confidence: 99%